(untitled) - Chan, Lois Mai. (Westport, Conn., 2005)
This book provides a basic understanding of the ever-evolving Library of Congress Classification system and its applications. After introducing the classification and giving a brief history of its development, the author presents readers with the general principles, structure, and format of the scheme. She then discusses and illustrates the use of tables. The main thrust of the new edition is the updated of the text according to policies governing current practices in using LCSH, and the highlighted relevance of LCSH in the global electronic environment. Part 3, completely rewritten, will include a chapter on FAST (Faceted Application of Subject Terminology), which is an LCSH-based controlled vocabulary for electronic resources
Keywords: Subject headings, Library of Congress,Tiêu đề chủ đề, Thư viện Quốc hội